William Shakespeare's Romeo & Juliet [videorecording (DVD)] - Luhrmann, Baz; DiCaprio, Leonardo; Danes, Claire, 1979-; Dennehy, Brian; Shakespeare, William, 1564-1616 (20th Century Fox Home Entertainment, 2006)
Baz Luhrmann's dazzling and unconventional adaptation of William Shakespeare's classic love story is spellbinding. The setting has been moved from its Elizabethan origins to the futuristic backdrop of Verona Beach with these star-crossed lovers.